2021
DOI: 10.3390/molecules26237194
|View full text |Cite
|
Sign up to set email alerts
|

New Sustainable Synthetic Routes to Cyclic Oxyterpenes Using the Ecocatalyst Toolbox

Abstract: Cyclic oxyterpenes are natural products that are mostly used as fragrances, flavours and drugs by the cosmetic, food and pharmaceutical industries. However, only a few cyclic oxyterpenes are accessible via chemical syntheses, which are far from being ecofriendly. We report here the synthesis of six cyclic oxyterpenes derived from ß-pinene while respecting the principles of green and sustainable chemistry. Only natural or biosourced catalysts were used in mild conditions that were optimised for each synthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The Grison group has shown that the remediation phytotechnologies, such as phytoextraction [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], rhizofiltration [ 28 , 29 , 30 , 31 ] and biosorption [ 32 , 33 , 34 , 35 , 36 ] generate biomass which can be turned into innovative ecocatalysts. Among the plant species that can be transformed, here, we selected the ones that were the richest in potassium ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Grison group has shown that the remediation phytotechnologies, such as phytoextraction [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], rhizofiltration [ 28 , 29 , 30 , 31 ] and biosorption [ 32 , 33 , 34 , 35 , 36 ] generate biomass which can be turned into innovative ecocatalysts. Among the plant species that can be transformed, here, we selected the ones that were the richest in potassium ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This innovative methodology is based on the use of biomass derived from metal-hyperaccumulating plants, used in the phytoextraction of metal contaminated sites, for the preparation of polymetallic catalysts suitable for applications in organic synthesis. This concept was successfully applied for important transformations such as the Lewis and/or Brønsted acid-catalyzed reactions (Diels–Alder reaction, Friedel–Crafts reaction, multicomponent reactions, cascade reactions) [ 54 , 55 , 56 , 57 , 58 ]; coupling reactions (Suzuki, Heck, Sonogashira and Ulmann type reactions) [ 59 , 60 , 61 , 62 , 63 , 64 ]; reductions (aminoreduction, selective reduction of αβ-unsaturated carbonyl compounds, nitro- and halogeno arenes) [ 65 , 66 , 67 ]; oxidations (epoxidations, oxidative cleavage, oxidations of alcohols) [ 68 , 69 , 70 ]; and tandem reactions (tandem carbonyl-ene cyclization, synthesis of substituted pyridines and oxidative iodination of ketones) [ 71 , 72 , 73 ]. However, examples on the use of ecocatalysis for C-P bond formation have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14][15] Perillyl alcohol can be converted to perillaldehyde and then to cumin aldehyde with the help of ecocatalyst. 16 Steam distillation is typically used to obtain essential oils. Despite being a traditional method, steam distillation has some advantages over other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical and clinical studies have demonstrated that perillyl alcohol is successful in fighting even the most aggressive types of cancer 9,12‐15 . Perillyl alcohol can be converted to perillaldehyde and then to cumin aldehyde with the help of ecocatalyst 16 …”
Section: Introductionmentioning
confidence: 99%